AKTIVITAS ANTIKANKER EKSTRAK AIR DAUN KELOR (Moringa oleifera L.) TERHADAP CELL LINE KANKER SERVIKS HELA DENGAN UJI SITOTOKSISITAS, APOPTOSIS, DAN JALUR INDUKSI APOPTOSIS BERDASARKAN EKSPRESI GEN P53 - , GANANG KUSUMA AHIMSA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Cervical cancer is one of the most prevalent cancer in the world. Until now, the use of chemotherapy in treating cancer causes many side effects sothe development of research using herbal medicine began.One of them isMoringa oleifera L. Moringa leaves are known consisting isothiocyanate compounds which are able to induce apoptosis, thus might have anticancer activity Objective: This study was conducted to determine the effect of cytotoxicity through apoptosis and induction of apoptotic pathways viap53 expression fromaqueous extracts of M. Oleifera L. against HeLa cervical cancer cells. Methods:Cytotoxicity assay was conducted on cancer cells that had been incubated for 24 hours using MTT reagent. Apoptotic testwas performedon cancer cells that have been incubated for 24 hours with test compounds using fluorescent microscopy and acridine orange fluorocrom. pathways of apoptosis induction observation was done on cancer cells that had been incubated for 24 hours with test compounds using light microscopy and staining immunohistochemistry. Results:This study showed thataqueous extract of M. oleifera leaves have cytotoxicity effect against cervical cancer cell line HeLa with IC50 value of 669.19ug/ml. Aqueous extract of M. oleifera leaves at a concentration of 660Î¼g/ml was able to induce apoptosis in HeLa cervical cancer cells. Aqueous extract of M. oleifera leaves at a concentration of 990Î¼g/ml was able to induce apoptosis through p53 pathway. Analysis using one-way ANOVA and post-hoc LSD showed that percentage of apoptosis and p53 expressionbetween test group (Aqueous extract of M. oleifera leaves) and negative control group were significantly different (P <0.05) Conclusion:Aqueous extract of M. Oleiferaleaves have cytotoxicityeffect against HeLa cervical cancer cells which occurred through apoptosis inductionby activation of p53